SOYBEAN PRODUCTIVITY AND YIELD STABILITY UNDER WATER-LIMITED CONDITIONS: EVIDENCE FROM CENTRAL ASIA (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
Soybean is increasingly viewed as a strategic crop for Central Asia because it combines high-quality protein with nitrogen fixation, supports crop-rotation benefits, and can reduce dependence on imported oilseed products. Yet soybean productivity in the region is strongly constrained by water scarcity, high evaporative demand, and growing climate variability. This article synthesizes evidence on soybean yield formation and yield stability under water-limited conditions in Central Asia, with emphasis on irrigated–non-irrigated contrasts, drought escape via maturity group selection, and drought tolerance traits targeted by breeding.
Keywords: Soybean; drought stress; yield stability; water-limited agriculture; Central Asia; irrigation efficiency; genotype.